Young Protagonists of Integral Sexual Education: Materializing Rights at School (Itinerarios Educativos, 2025)
This paper presents a university extension project developed within the framework of the Extension Activities Strengthening Program (PROFAE). The initiative was carried out in 2024 by teachers and students of the University Teacher Training Program in Biological Sciences of the Faculty of Forest Sciences, National University of Misiones (FCF–UNaM), in articulation with teachers from four secondary schools in the city of Eldorado (Misiones). Its purpose was to strengthen the implementation of Integral Sexual Education (ISE) through an interdisciplinary and participatory proposal that included reflection spaces, dialogic sessions and recreational activities aimed at promoting meaningful learning, questioning stereotypes and fostering informed decision-making.The project is grounded in a critical extension approach, where extension students engage actively with educational communities, acknowledging previous knowledge, promoting rights and building networks of youth promoters. In this sense, the initiative sought to contribute to a more equitable and contextualized implementation of ISE in schools through collaborative work, knowledge dialogue and the strengthening of practices that promote healthy lifestyles and the full exercise of sexual and reproductive rights.
Keywords: Integral Sexual Education; university extension; secondary schools